Economic analysis of commercial organic and conventional vegetable farming in Kathmandu Valley - Shrestha, Kamal; Shrestha, Gautam; Pandey, Pradyumna R (Journal of Agriculture and Environment, 2014)
Economics of a farming system is the key determinant of its sustainability. Organic and conventional farming systems are two distinct types of production systems having contrasting farm management practices and output price as well. Furthermore, organic farming system is promoted for environmental protection and conventional farming system is cursed for the environmental degradation. The present study was conducted to compare the economics of organic and conventional vegetable production in Kathmandu valley. Thirty farmers each involved in commercial organic and conventional vegetable farming were selected randomly for the study. Data were collected through survey method using semi-structured questionnaire. The estimated per ropani per year cost of cultivation of vegetables in the organic farm (NPR 69,170) was lesser than in conventional farm (NPR 1,00,562). The gross return per ropani in a year in the organic vegetable farm (NPR 1,01,536) was significantly lesser than from conventional farms (NPR 1,35,747). Benefit to cost ratio (BCR) was higher in organic farm (1.47:1) in comparison to conventional farm (1.35:1). This study revealed that organic vegetable farming was more profitable than conventional vegetable farming in Kathmandu valley. To expand commercial agriculture: quality inputs, input and output price stability, co-operative or corporative marketing should be promoted.